Subpopulations Within Juvenile Psoriatic Arthritis: A Review of the Literature. Issue 2 (2006) - Stoll, Matthew L.; Nigrovic, Peter A.
Abstract : The presentation of juvenile psoriatic arthritis (JPsA) has long been recognized to be clinically heterogeneous. As the definition of JPsA expanded to accommodate atypical manifestations of psoriasis in young children, studies began to reflect an increasingly clear biphasic distribution of age of onset, with peaks in the first few years of life and again in early adolescence. These two subpopulations differ in gender ratio, pattern of joint involvement, laboratory findings and potentially response to therapy. Intriguingly, a similar distribution of age of onset has been observed in juvenile rheumatoid arthritis (JRA), and correlates with patterns of HLA association. While a secure classification of subpopulations within JPsA awaits improved pathophysiologic understanding, future research must consider the possibility that different disease mechanisms may be operative in distinct subsets of patients with this disorder.